The effect of chromium addition on fluidity, microstructure and mechanical properties of aluminum lm6 cast alloy - Ahmad, R (Madridge Publishers, 2018)
This article investigates the effects of Cr addition on microstructure, mechanical properties and fluidity of as-cast aluminum (LM6) alloy. Presence of 0.05, 0.1 and 0.15 wt.% Cr were add to LM6 melting greensand cast. There is no relationship between Cr addition and Si morphology. The Cr addition had modified the Fe intermetallics to irregular shapes. The mechanical properties such as toughness and hardness of LM6 had increase with increase the Cr value. The β-phases have largest surface to volume ratio, hence they have the largest interfacial region with the melt and are the most detrimental intermetallic to the fluidity. The sludge formation and consuming Si and shifts the local chemical composition of the melt to the aluminum side of the phase diagram increase with Cr addition, which has lower fluidity than base alloy.